Pemanfaatan Aplikasi Canva dalam Proses Pembelajaran Bahasa Arab di MAN Gunung Padang Panjang - Amrina; Adam Mudinillah; Ega Putri Handayani (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2021)
This article examines the use of Canva software in the Arabic learning process. Canva is a graphic design application that helps users to more easily design various types of creativity from the inspiration of their own thoughts. In the learning process, this software is indispensable. This software arose from the thought of designing tools that help produce work in learning, and can be done anywhere. This is of course in line with the learning needs during the COVID-19 virus pandemic, where the government prefers to carry out activities at home. The subject of the research is a teacher who has teaching experience in class XI MAN Gunung Padang Panjang. Research is directed at describing the steps, features and benefits of learning to use Canva. The results of the study found that teachers followed a step-by-step tutorial to use Canva which has various features, so that users can use it to produce a work in the form of a poster. Teachers feel the benefits of using Canva more towards graphic design in learning. Not only learning languages, Canva is proven to encourage students' creativity.